Application and interpretation of histocompatibility data in liver transplantation. Issue 5 (October 2017) - Wesson, Russell N.; Etchill, Eric W.; Garonzik-Wang, Jacqueline
Abstract : Purpose of review: There has been a resurgence of interest in histocompatibility as it applies to liver transplantation. The association of persistent and de-novo donor specific antibody (DSA) and outcomes after liver transplantation continues to be investigated. Recent findings: Consensus continues to evolve regarding the existence of acute and chronic antibody-mediated rejection (AMR) and pathogenicity of DSA and associated pathologic findings after liver transplantation. The presence of persistent high level, complement fixing DSA or emergence of de novo, Class II DSA has been associated with rejection and worse long-term graft and patient survival. Significant adverse associations of DSA extend to patients after simultaneous liver kidney (SLK) transplant as well as in pediatric recipients of liver transplantation. A higher degree of HLA incompatibility has been recently associated with worse outcomes in living donor liver transplant. Summary: In summary, recent consensus guidelines describe and recognize the existence of acute and chronic AMR and provide a basis upon which to build further investigation. Important adverse outcomes including decreased survival, allograft failure and liver fibrosis have been linked to the presence of DSA. Routine donor and recipient HLA typing and DSA assessment will facilitate diagnosis and provide for baseline data, which may help guide future management. Future investigations may help to clarify the role of therapeutic interventions